2022
DOI: 10.1128/msystems.00451-22
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Production in Alkanna tinctoria Links Plant Development with the Recruitment of Individual Members of Microbiome Thriving at the Root-Soil Interface

Abstract: Previous studies have shown that individual, isolated microorganisms may influence secondary metabolism of plants and induce or stimulate the production of medicinally relevant secondary metabolism. Here, we analyzed the microbiome-metabolome linkage of the medicinal plant Alkanna tinctoria , which is known to produce valuable compounds, particularly the naphthoquinones alkannin and shikonin and their derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Under conditions of biotic stress, the idea of a “cry for help” has been discussed as a way in which plants deploy metabolite signals to recruit beneficial microbes to help alleviate both abiotic and biotic stresses ( 24 27 ). While much of the research enumerating examples of the “cry for help” hypothesis has measured root exudates, root metabolites also provide an important factor in shaping microbial communities ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of biotic stress, the idea of a “cry for help” has been discussed as a way in which plants deploy metabolite signals to recruit beneficial microbes to help alleviate both abiotic and biotic stresses ( 24 27 ). While much of the research enumerating examples of the “cry for help” hypothesis has measured root exudates, root metabolites also provide an important factor in shaping microbial communities ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of biotic stress the idea of a “cry for help” has been discussed as a way in which plants deploy metabolite signals to recruit beneficial microbes to help alleviate both abiotic and biotic stresses (Dicke & Baldwin, 2010; Liu et al, 2021; Rizaludin et al, 2021; Rolfe et al, 2019). While much of the research enumerating examples of the “cry for help” hypothesis has measured root exudates – root metabolites also provide an important factor in shaping microbial communities (Bourceret et al, 2022; Csorba et al, 2022; DeWolf et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…(French marigold) [76] Alkannin/shikonin Labrys Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium Penicillium (fungus) Roots Alkanna tinctoria L . [77] * Alkannin/shikonin Chitinophaga sp. Allorhizobium sp.…”
Section: Microbe-increased Production Of Terpenoidsmentioning
confidence: 99%
“…The roots of Alkanna tinctoria L. are rich in alkannin and shikonin, which are two enantiomeric polyphenols that induce excellent cytotoxicity in cancer cells [77] . A recent study of A. tinctoria grown in a greenhouse revealed that the plant developmental stage influenced both the metabolite contents and the plant root microbial diversity, and that the bacterial genera Labrys and Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium as well as four species of the fungal genus Penicillium were positively correlated with higher contents of alkannin and shikonin [77] .…”
Section: Microbe-increased Production Of Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation